Prenatal Diagnosis of a Ventral Abdominal Wall Defect. - Beam, Kristyn; Wojcik, Monica H; Agrawal, Pankaj B; Smithers, Charles; Estroff, Judy (Neoreviews, 2020)
Keywords: Abnormalities, Multiple; Echocardiography; Fatal Outcome; Female; Hernia, Abdominal; Hernia, Diaphragmatic; Hernia, Ventral; Humans; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prenatal Diagnosis; Ultrasonography, Prenatal

Monoallelic and biallelic CREB3L1 variant causes mild and severe osteogenesis imperfecta, respectively. - Keller, Rachel B; Tran, Thao T; Pyott, Shawna M; Pepin, Melanie G; Savarirayan, Ravi; McGillivray, George; Nickerson, Deborah A; Bamshad, Michael J; Byers, Peter H (Genet Med, 2018)
PurposeOsteogenesis imperfecta (OI) is a heritable skeletal dysplasia. Dominant pathogenic variants in COL1A1 and COL1A2 explain the majority of OI cases. At least 15 additional genes have been identified, but those still do not account for all OI phenotypes that present. We sought the genetic cause of mild and lethal OI phenotypes in an unsolved family.MethodsWe performed exome sequencing on seven members of the family, both affected and unaffected.ResultsWe identified a variant in cyclic AMP responsive element binding protein 3-like 1 (CREB3L1) in a consanguineous family. The variant caused a prenatal/perinatal lethal OI in homozygotes, similar to that seen in OI type II as a result of mutations in type I collagen genes, and a mild phenotype (fractures, blue sclerae) in multiple heterozygous family members. CREB3L1 encodes old astrocyte specifically induced substance (OASIS), an endoplasmic reticulum stress transducer. The variant disrupts a DNA-binding site and prevents OASIS from acting on its transcriptional targets including SEC24D, which encodes a component of the coat protein II complex.ConclusionThis report confirms that CREB3L1 is an OI-related gene and suggests the pathogenic mechanism of CREB3L1-associated OI involves the altered regulation of proteins involved in cellular secretion.
Keywords: Alleles; Amino Acid Sequence; Collagen Type I; Cyclic AMP Response Element-Binding Protein; DNA Mutational Analysis; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Mutation; Nerve Tissue Proteins; Osteogenesis Imperfecta; Pedigree; Phenotype; Radiography; Sequence Analysis, DNA; Severity of Illness Index; Ultrasonography, Prenatal

Visceral myopathy: Clinical and molecular survey of a cohort of seven new patients and state of the art of overlapping phenotypes. - Moreno, Carolina Araujo; Metze, Konradin; Lomazi, Elizete Aparecida; Bertola, Débora Romeo; Barbosa, Ricardo Henrique Almeida; Cosentino, Viviana; Sobreira, Nara; Cavalcanti, Denise Pontes (Am J Med Genet A, 2016)
Visceral motility dysfunction is a key feature of genetic disorders such as megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS, MIM moved from 249210 to 155310), chronic intestinal pseudo-obstruction (CIPO, MIM609629), and multisystemic smooth muscle dysfunction syndrome (MSMDS, MIM613834). The genetic bases of these conditions recently begun to be clarified with the identification of pathogenic variants in ACTG2, ACTA2, and MYH11 in individuals with visceral motility dysfunction. The MMIHS was associated with the heterozygous variant in ACTG2 and homozygous variant in MYH11, while the heterozygous variant in ACTA2 was observed in patients with MSMDS. In this study, we describe the clinical data as well as the molecular investigation of seven individuals with visceral myopathy phenotypes. Five patients presented with MMIHS, including two siblings from consanguineous parents, one had CIPO, and the other had MSMDS. In three individuals with MMIHS and in one with CIPO we identified heterozygous variant in ACTG2, one being a novel variant (c.584C>T-p.Thr195Ile). In the individual with MSMDS we identified a heterozygous variant in ACTA2. We performed the whole-exome sequencing in one sibling with MMIHS and her parents; however, the pathogenic variant responsible for her phenotype could not be identified. These results reinforce the clinical and genetic heterogeneity of the visceral myopathies. Although many cases of MMIHS are associated with ACTG2 variants, we suggest that other genes, besides MYH11, could cause the MMIHS with autosomal recessive pattern. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Actins; Child, Preschool; Colon; Consanguinity; DNA Mutational Analysis; Fatal Outcome; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Phenotype; Polymorphism, Single Nucleotide; Treatment Outcome; Ultrasonography, Prenatal; Urinary Bladder